Finally, the sounds of nineteen-century Mexico are no longer so distant: what implies listening again to the Te Deum laudamus (1835) by José Antonio Gómez? - Lazos, John G. (2023)
The musical practice of the Mexican 19th century continues to be a pending topic in our fields of study as well as in the musical scene. Despite this, the name of José Antonio Gómez y Olguín is beginning to resound. The resurgence of this 19th century philharmonic musician is largely due to the approach and study of first-hand sources. However, even with a clearer idea of his life and work, his main legacy, his works, are still absent on our stages.I am interested in narrating the factors that have kept at a distance a crucial period of our musical history. For example, how in 1835 a Federal Law determined a series of events that culminated in the Metropolitan Cathedral. The Cabildo decided to receive general Antonio López de Santa-Anna with a Te Deum. Then, the second organist, José Antonio Gómez proposed to write a work with soloists, choir and large orchestra according to the moment. In the early days of independent Mexico, Gómez was playing for his future within the most important church in the country and, by extension, in the secular sphere. Two hundred years later the Xalapa Symphony Orchestra performed his Te Deum laudamus with great success in September 2022.